Hydraulic cement composition
The hydraulic cement composition incorporating a water-soluble vinyl copolymer dispersant effectively addresses the challenges of reduced flowability and strength in fluoride-containing cements, enhancing the performance of both fluoride-containing and fluoride-free cements.
Patent Information
- Application Number
- JP2023179887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Hydraulic cement compositions containing inorganic fluoride as a flux agent often experience reduced flowability and flow retention, leading to decreased initial strength of the cured concrete body, especially when conventional cement dispersants are used.
A hydraulic cement composition utilizing a water-soluble vinyl copolymer as a cement dispersant, specifically copolymerized from monomers A to D with a defined molecular structure and molecular weight range, is employed to enhance flowability, flow retention, and initial strength development.
The use of the water-soluble vinyl copolymer dispersant significantly improves the flowability and initial strength of the concrete, while maintaining flow retention, even when using cement containing fluoride, thereby addressing the limitations of conventional dispersants.
Smart Images

Figure 2025060342000001 
Figure 2025060342000002 
Figure 2025060342000003
Abstract
Description
Detailed Description of the Invention [Technical field]
[0001] The present invention relates to a hydraulic cement composition. More specifically, the present invention relates to a hydraulic cement composition that can ensure high quality even when a cement containing an inorganic fluoride (hereinafter, referred to as fluoride) is used as a flux newly added in the cement manufacturing process. [Background technology]
[0002] In recent years, a technique of adding fluoride as a flux to lower the calcination temperature has been known for the purpose of saving energy in the calcination process of cement production. However, when a hydraulic cement composition (e.g., Patent Document 4) is produced using a conventionally known cement dispersant (e.g., Patent Documents 1, 2, and 3) using a quality cement containing the fluoride, there is a problem that the quality of the hydraulic cement composition is relatively deteriorated. Specifically, compared with a cement composition not containing fluoride, the initial fluidity of the hydraulic cement composition containing fluoride tends to decrease and the fluidity retention over time tends to decrease significantly. In order to ensure the target fluidity and workability, it is necessary to add a considerably large amount of the conventionally known cement dispersant, which causes a problem that the setting time is delayed and the initial strength of the hydraulic cement composition hardened body (e.g., concrete hardened body) is reduced.
[0003] Under such a background, some proposals have been disclosed to add certain cement additives during mixing, particularly when producing hydraulic cement compositions using fluoride-containing cement (e.g., Patent Documents 5 and 6).
[0004] However, when a hydraulic cement composition is actually prepared using cement in which fluoride from the flux remains, even if a conventionally known polycarboxylic acid cement dispersant (or additive) is used, the performance of the role that the dispersant itself should originally play (the performance of combining the three performances of initial fluidity, fluidity retention, and early strength development, hereinafter referred to as the present purpose) is not sufficient, and there is a demand for a proposal for a hydraulic cement composition using a cement dispersant that combines the performance of these three items and is excellent in practicality and economy. In other words, when a hydraulic cement composition is prepared using various conventionally known cement dispersants for this purpose, there is a problem that each of them has its own problems and fully satisfactory performance is not obtained. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 5-11057 (Patent Publication) [Patent Document 2] JP 11-171619 A (Patent Publication) [Patent Document 3] JP 2003-2720 (Patent Publication) [Patent Document 4] JP 2013-112565 (Patent Publication) [Patent Document 5] JP 2017-178775 (Patent Publication) [Patent Document 6] JP 2017-222553 (Patent Publication) DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to provide a hydraulic cement composition which is excellent in fluidity, fluid retention and early strength development of the hardened body, even if it is a mortar or concrete using a cement containing fluoride or a cement not containing fluoride. [Means for solving the problem]
[0007] As a result of research conducted by the present inventors to solve the above problems, they have found that a hydraulic cement composition using a cement dispersant made of a water-soluble vinyl copolymer having a specific molecular skeleton is a suitable means for satisfying the above requirements.
[0008] That is, the present invention relates to a hydraulic cement composition comprising at least cement, aggregate, water, and the following cement dispersant, characterized in that the content of the cement dispersant per 100 parts by mass of cement is 0.05 to 2.5 parts by mass. Cement dispersant: A vinyl copolymer obtained by copolymerizing in an aqueous solution a monomer A shown in the following Chemical formula 1, a monomer B shown in the following Chemical formula 2, a monomer C shown in the following Chemical formula 3, and a monomer D shown in the following Chemical formula 4, the copolymerization ratio converted into monomers being represented by the following monomer A shown in the following Chemical formula 1 / monomer B shown in the following Chemical formula 2 / monomer C shown in the following Chemical formula 3 / monomer D shown in the following Chemical formula 4=55-88 / 0.5-10 / 0.5-10 / 8-25 (mol%, total 100), and the cement dispersant is composed of a water-soluble vinyl copolymer having a mass average molecular weight in the range of 3,000-100,000.
[0009] [ka] [ka] [ka] [ka]
[0010] (In Chemical Formula 1 to Chemical Formula 4, R 1 ,R 2 ,R 1 ,R 3 ,R 4 ,:H or CH 3 . R 5: An alkyl group having 1 to 3 carbon atoms. M 1 :Hydrogen or an alkali metal or an alkaline earth metal. n: an integer between 1 and 3. m: An integer between 4 and 95.
[0011] The water-soluble vinyl copolymer used as a cement dispersant in the present invention is a vinyl copolymer obtained by aqueous radical copolymerization of monomer A represented by Chemical formula 1, monomer B represented by Chemical formula 2, monomer C represented by Chemical formula 3, and monomer D represented by Chemical formula 4.
[0012] Examples of the monomer A represented by Chemical formula 1 include 1) methacrylic acid or an alkali metal salt or an alkaline earth metal salt of methacrylic acid, and 2) acrylic acid or an alkali metal salt or an alkaline earth metal salt of acrylic acid. Among these, methacrylic acid and / or sodium methacrylic acid are preferred.
[0013] Examples of the monomer B represented by Chemical formula 2 include 1) alkali metal salts and alkaline earth metal salts of methallylsulfonic acid, and 2) alkali metal salts and alkaline earth metal salts of allylsulfonic acid. The purpose of using the monomer B is to adjust the molecular weight during polymerization of the vinyl copolymer, and to enhance the cement dispersion function by partially introducing sulfonic acid groups into the molecular skeleton to construct a copolymer with less setting retardation than the above-mentioned carboxylic acid group alone as an anion group. The introduction of sulfonic acid groups is one of the features of the present invention, and among them, it is preferable to use sodium methallylsulfonate.
[0014] Examples of the monomer C represented by Chemical formula 3 include 1) ethylene glycol monoacrylate (hereinafter referred to as HEA), diethylene glycol monoacrylate, and triethylene glycol monoacrylate, and 2) ethylene glycol monomethacrylate (hereinafter referred to as HEMA), diethylene glycol monomethacrylate, and triethylene glycol monomethacrylate.
[0015] In the present invention, the reason for introducing (meth)acrylic acid monoesters as monomer C into the molecular skeleton of the vinyl copolymer is to utilize the property that when the vinyl copolymer is added to the cement formulation, the ester group is hydrolyzed over time by the alkaline component of the cement, increasing the proportion of carboxyl groups. In other words, it is used to impart a slump loss prevention function to the molecular skeleton of the copolymer itself. In the present invention, among them, the above-mentioned HEA, the above-mentioned HEMA, and diethylene glycol monomethacrylate are preferable.
[0016] In the present invention, as monomer D shown in Chemical Formula 4, two types of alkoxy (having 1 to 3 carbon atoms) polyethylene glycol (meth)acrylate monomers with different molar numbers, with the addition molar number of ethylene oxide ranging from 4 to 95, preferably from 5 to 85, can be used.
[0017] Specifically, within the range of the addition molar number (m) of ethylene oxide contained in monomer D, a monomer in the range of 5 to 30 molar numbers (referred to as monomer E) and a monomer in the range of 31 to 85 molar numbers (referred to as monomer F), two types of monomer components, are preferably contained together at a predetermined ratio (however, the copolymerization molar ratio of E and F is E < F) during the copolymerization reaction with other comonomers. This synthesis method is also one of the characteristics of the cement dispersant according to the present invention.
[0018] The water-soluble vinyl copolymer used as the cement dispersant in the present invention is obtained by radical copolymerization of vinyl monomers containing constitutional units A to D (however, the monomer D component includes the monomer E component and the monomer F component) in the presence of a radical initiator so as to have a predetermined copolymerization ratio. The radical copolymerization can be carried out in an aqueous solution using a water-soluble radical initiator.
[0019] As the copolymerization method of the water-soluble vinyl copolymer used in the present invention, for example, the following two methods 1) or 2) can be mentioned, but it is not limited thereto. In the present invention, from the viewpoint of obtaining a copolymer with a relatively narrow molecular weight distribution, method 1) is preferable. 1) In advance, in a mixing vessel, each of the specified vinyl monomers and a molecular weight regulator are dissolved and mixed in water to prepare an aqueous solution (G) containing 30 to 55 mass% of each vinyl monomer in total. Meanwhile, in a separate mixing vessel, an aqueous solution (H) of a radical initiator dissolved in water is prepared. Next, using a separate polymerization reaction vessel, the aqueous solutions (G) and (H) are dropped separately and simultaneously into the polymerization reaction vessel for a specified time under a nitrogen gas atmosphere, while a radical copolymerization reaction is continued under a nitrogen gas atmosphere at 60 to 75°C for 4 to 6 hours, thereby obtaining a water-soluble vinyl copolymer copolymerized at a high polymerization rate. 2) Each of the specified vinyl monomers and the molecular weight modifier is dissolved in water to prepare an aqueous solution containing 20 to 45 mass% of each vinyl monomer in total. Next, a radical initiator is added to the aqueous solution in a nitrogen gas atmosphere, and a radical copolymerization reaction is carried out at 55 to 70°C for 4 to 6 hours to obtain an aqueous solution of a water-soluble vinyl copolymer copolymerized at a high polymerization rate.
[0020] As the radical initiator, a water-soluble initiator such as a persulfate, such as potassium persulfate, sodium persulfate, or ammonium persulfate, or 2,2-azobis(2-amidinopropane) dihydrochloride can be used. Furthermore, an aqueous redox initiator in which hydrogen peroxide is combined with a reducing substance such as L-ascorbic acid or a sulfite can also be used.
[0021] As the molecular weight regulator, a water-soluble thiol-based chain transfer agent such as mercaptoethanol, thioglycolic acid, 3-mercaptopropionic acid, or thiomalic acid can be used. In the present invention, the (meth)allylsulfonate salt used as the monomer B is a substance that simply acts as a comonomer and exhibits properties as a weak chain transfer agent in aqueous radical polymerization, so it is preferable to use it in combination with a strong thiol-based chain transfer agent (e.g., 3-mercaptopropionic acid) that is compatible with it. The amount of the thiol-based chain transfer agent used is appropriately adjusted according to the target molecular weight of the copolymer.
[0022] The water-soluble vinyl copolymer of the present invention thus obtained has, as its constituent units, a copolymerization ratio calculated as monomers represented by monomer A / monomer B / monomer C / monomer D=55-88 / 0.5-10 / 0.5-10 / 8-25 (mol %, total 100).
[0023] As described above, when the monomer D is a monomer D (E+F) including a monomer E having an added mole number of ethylene oxide in the range of 5 to 30 and a monomer F having an added mole number in the range of 31 to 80, the copolymerization ratio converted into monomers is more preferably monomer A / monomer B / monomer C / monomer D (E+F)=60-80 / 1-7 / 1-8 / 9-24 (mol %, total 100) as the specific copolymer of the present invention. The mass average molecular weight of the vinyl copolymer is in the range of 3,000 to 100,000 (gel permeation chromatography (GPC), calculated as polyethylene glycol, the same applies below), and is preferably in the range of 5,000 to 80,000.
[0024] The water-soluble vinyl copolymer used as a cement dispersant in the present invention is obtained by copolymerizing each of the vinyl monomers exemplified above in a predetermined ratio, and a copolymer having a copolymerization ratio and a mass average molecular weight outside the predetermined range does not provide the sufficient effect of the present invention. In this case, other monomers may be copolymerized as needed as long as they do not impair the effect of the present invention. For example, acrylic acid methyl ester and (meth)acrylamide can be mentioned, and these are usually used within a range of 10 mol% or less of the total monomers.
[0025] In the present invention, the cement may be Portland cement or a mixed cement containing Portland cement and a fine powder admixture. Portland cement may be any of various types of Portland cement, such as ordinary cement, high-early-strength cement, ultra-high-early-strength cement, moderate-heat cement, and low-heat cement, but general-purpose ordinary cement is preferred. In addition, fine powder admixture may be granulated blast furnace slag, granulated fly ash, granulated silica fume, etc., and various mixed cements, such as blast furnace cement, fly ash cement, and silica fume cement, which are distributed on the market as cement prepared by mixing a predetermined amount of various fine powders with Portland cement in advance, may be used. Among the mixed cements, blast furnace cement is preferred, and specifically, it can be effectively used for any of the types of blast furnace cement A, B, and C, which have different fine powder content ratios.
[0026] In addition, the present invention can be effectively used for Portland cement containing fluoride in the range of 0.05 to 10 mass %.Furthermore, it can be effectively used for mixed cement obtained by mixing the Portland cement with a fine powder admixture, specifically, for blast furnace cement containing residual flux.
[0027] The fluoride may be an inorganic compound selected from the group consisting of KF, CaF2, NaF, BaF2, MgF2, Na2SiF2, MgSiF2, etc., and among these, fluorides consisting of KF or CaF2 are well known.
[0028] The hydraulic cement composition of the present invention is a composition containing at least cement, aggregate, water and the above-mentioned cement dispersant, and includes mortar using only fine aggregate as aggregate and concrete using fine aggregate and coarse aggregate as aggregate. The content of the cement dispersant used is in the range of 0.05 to 2.5 parts by mass, preferably 0.1 to 2 parts by mass, in terms of solid matter, per 100 parts by mass of cement. In addition, the unit water amount is 120 to 180 kg / m 3This is also preferable when preparing and producing concrete with a water-binder ratio in the range of 20 to 65%.
[0029] In preparing the hydraulic cement composition, other agents may be used in combination depending on the purpose. Such other additives include air entraining agents, antifoaming agents, shrinkage reducing agents, hardening accelerators, hardening retarders, waterproofing agents, preservatives, etc. In addition, the method of use is usually to add them together with the mixing water when preparing the hydraulic cement composition, but they can also be added later.
[0030] The cement dispersant used in the present invention was constructed based on the synthesis of a water-soluble polymer with a specific molecular structure, and is characterized by the following 1) to 3). Although not conclusive, the characteristics are that the synthesis requirements include 1) the use of monomer B to introduce a sulfonic acid group into the molecular skeleton, 2) the use of monomer C to introduce a short-chain ester group that is easily hydrolyzed over time by an alkaline component that precipitates at the cement hydration stage into the molecular skeleton, and 3) the use of monomer D to introduce a relatively long PEG chain and a relatively short PEG chain into the molecular skeleton. Effect of the Invention
[0031] According to the present invention, the hydraulic cement composition using the cement dispersant made of the water-soluble vinyl copolymer as described above has a high ability to exhibit the intended effect, whether it is made of normal cement or a blended cement, i.e., it has the characteristics of imparting excellent fluidity to normal strength concrete as well as high strength concrete, reducing slump loss, and at the same time, exhibiting excellent early strength of the hardened concrete.
[0032] Examples will be given below to more specifically illustrate the configuration and effects of the present invention, but the present invention is not limited to these examples. In the following examples, % means % by mass, and parts means parts by mass, unless otherwise specified. EXAMPLES
[0033] Test Section 1 (Synthesis of Water-Soluble Vinyl Copolymers as Cement Dispersants) Water-soluble vinyl copolymers used in the examples Vinyl copolymer (P-1) On the other hand, 62 parts (0.72 moles) of methacrylic acid, 5.2 parts (0.03 moles) of sodium methallylsulfonate, 5.2 parts (0.03 moles) of ethylene glycol monoacrylate, 31 parts (0.06 moles) of methoxypoly (10 moles) ethylene glycol methacrylate, 416 parts (0.20 moles) of methoxypoly (45 moles) ethylene glycol methacrylate, 2.4 parts of 3-mercaptopropionic acid, 230 parts of water, and 45 parts of a 30% aqueous solution of sodium hydroxide were added to the monomer mixing vessel V1, and the mixture was stirred and mixed and dissolved. On the other hand, 62 parts of water, 7 parts of sodium persulfate, and 1.2 parts of 3-mercaptopropionic acid were added to the radical initiator dissolving mixing vessel V2, and the mixture was uniformly mixed and dissolved. Next, 120 parts of water was added to the polymerization reactor V3, and the atmosphere was replaced with nitrogen. The temperature of the reaction system was kept at 70°C while stirring, and the solution was dropped from the mixing vessel V1 to the reaction vessel V3 over 3 hours using a metering pump. At the same time, the solution was dropped from the mixing vessel V2 on a separate route to the reaction vessel V3 over 4 hours using a metering pump. After the dropwise addition, the mixture was aged for 2 hours to complete the polymerization reaction. Next, the temperature of the reaction system was cooled to 40°C, and then 15 parts of a 30% aqueous solution of sodium hydroxide was added to neutralize the acid decomposition product, and a reaction product with a polymerization rate of over 98% was obtained. Analysis of this reaction product revealed that it was a water-soluble vinyl copolymer (P-1) having a mass average molecular weight of 39,000, with the total structural units being comprised of the following ratios: structural units formed from sodium methacrylate / structural units formed from sodium methallylsulfonate / structural units formed from ethylene glycol monoacrylate / structural units formed from methoxypoly(10 mol)ethylene glycol methacrylate / structural units formed from methoxypoly(45 mol)ethylene glycol methacrylate = 70 / 3 / 4 / 6 / 17 (mol %, total of all structural units is 100 mol %).
[0034] Vinyl copolymer (P-2) As a result of synthesis and analysis in the same manner as in the vinyl copolymer (P-1), it was found that the copolymer was a water-soluble vinyl copolymer (P-2) having a mass average molecular weight of 57,000 and having, among all the structural units, the ratio of structural units formed from sodium methacrylate / structural units formed from sodium methallylsulfonate / structural units formed from ethylene glycol monomethacrylate / structural units formed from methoxypoly(20 mol)ethylene glycol methacrylate / structural units formed from methoxypoly(68 mol)ethylene glycol methacrylate=76 / 6 / 4 / 3 / 11 (mol %, total of all structural units is 100 mol %).
[0035] Vinyl copolymer (P-3) As a result of synthesizing and analyzing in the same manner as the vinyl copolymer (P-1), it was found that the water-soluble vinyl copolymer (P-3) had a mass average molecular weight of 36,700 and contained, among all the structural units, the structural units formed from sodium methacrylate / structural units formed from sodium acrylate / structural units formed from sodium allylsulfonate / structural units formed from ethylene glycol monoacrylate / structural units formed from methoxypoly(10 mol)ethylene glycol methacrylate / structural units formed from methoxypoly(45 mol)ethylene glycol methacrylate in a ratio of 60 / 10 / 3 / 4 / 7 / 16 (mol %, total of all structural units is 100 mol %).
[0036] Synthesis of vinyl copolymer (P-4) On the other hand, 62 parts (0.72 moles) of methacrylic acid, 5.2 parts (0.03 moles) of sodium methallylsulfonate, 5.2 parts (0.04 moles) of ethylene glycol monomethacrylate, 445 parts (0.21 moles) of methoxypoly (addition mole number 45 moles) ethylene glycol methacrylate, 2.4 parts of 3-mercaptopropionic acid, 230 parts of water, and 45 parts of a 30% aqueous solution of sodium hydroxide were charged into a monomer mixing vessel V1, and stirred and mixed to dissolve. On the other hand, 62 parts of water, 7 parts of sodium persulfate, and 1.2 parts of 3-mercaptopropionic acid were charged into a radical initiator dissolving mixing vessel V2, and mixed and dissolved uniformly. Next, 120 parts of water were charged into a polymerization reaction apparatus V3, and the atmosphere was replaced with nitrogen. The temperature of the reaction system was kept at 70°C while stirring, and the solution was dropped from the mixing vessel V1 to the reaction vessel V3 over a period of 3 hours using a metering pump. At the same time, the solution was dropped into the reactor V3 from a mixing vessel V2 on a separate route over a period of 4 hours using a metering pump. After the dropwise addition, the mixture was aged for 2 hours to complete the polymerization reaction. The temperature of the reaction system was then cooled to 40°C, and 15 parts of a 30% aqueous solution of sodium hydroxide was added to neutralize the acid decomposition product, resulting in a reaction product with a polymerization rate of over 98%. When this reaction product was analyzed by NMR, GPC, water content, loss on drying, etc., it was found to be a water-soluble vinyl copolymer (P-4) with a mass average molecular weight of 42,000, containing, among all structural units, the following ratio of structural units: sodium methacrylate / sodium methallyl sulfonate / ethylene glycol monomethacrylate / methoxypoly(45 mol)ethylene glycol methacrylate=72 / 3 / 4 / 21 (mol %, total of all structural units is 100 mol %).
[0037] Vinyl copolymer (P-5) As a result of synthesizing and analyzing in the same manner as the vinyl copolymer (P-4), it was found that the copolymer was a water-soluble vinyl copolymer (P-5) having a mass average molecular weight of 62,400 and having, among all the structural units, the ratio of structural units formed from sodium methacrylate / structural units formed from sodium allylsulfonate / structural units formed from ethylene glycol monomethacrylate / structural units formed from methoxypoly(68 mol)ethylene glycol methacrylate=76 / 5 / 6 / 13 (mol %, total of all structural units is 100 mol %).
[0038] Water-soluble vinyl copolymer used in the comparative examples Water-soluble vinyl copolymers (R-1) to (R-5) As a result of synthesis and analysis in the same manner as (P-1), water-soluble vinyl copolymer (R-1) was obtained. As a result of synthesis and analysis in the same manner, water-soluble vinyl copolymers (R-2) to (R-5) were obtained. The details of each water-soluble vinyl copolymer are summarized in Table 1.
[0039] [Table 1]
[0040] In Table 1, *1: Sodium methacrylate *2: Sodium acrylate *3: Sodium methallyl sulfonate *4: Sodium allylsulfonate *5: Ethylene glycol monoacrylate *6: Ethylene glycol monomethacrylate *7: Methoxypoly (addition mole number 10 moles) ethylene glycol methacrylate ester *8: Methoxypoly (addition mole number 20 moles) ethylene glycol methacrylate ester *9: Methoxypoly (addition mole number 45 moles) ethylene glycol methacrylate ester *10: Methoxypoly (addition mole number 68 moles) ethylene glycol methacrylate ester *11: Methoxypoly (addition mole number 120 moles) ethylene glycol methacrylate ester
[0041] Test Category 2 (Preparation and Evaluation of Concrete) Examples 1 to 5 Using the water-soluble vinyl copolymer (P-1) of the present invention prepared in Test Section 1 under the mixing conditions (mixture number 1, containing calcium fluoride) shown in Table 2, a 50-liter pan-type forced mixer was used to mix ordinary Portland cement (density = 3.16 g / cm) containing CaF2. 3 , 1 part of CaF2 was added to 100 parts of cement), fine aggregate (river sand, density = 2.58 g / cm 3 ), mixing water (tap water) and the necessary amount of antifoaming agent and air content regulator were added and mixed for 90 seconds until the slurry became uniform. Next, coarse aggregate (crushed stone, density = 2.68 g / cm 3 ) was added and mixed for 60 seconds. The water-containing component contained in the water-soluble vinyl copolymer of the present invention was added while being diluted with the mixing water as a part of the mixing water, and concrete of Example 1 was prepared with a water-cement ratio of 50%, a target slump of 18±1 cm, and a target air content of 4±1%. Similarly, concrete of Examples 2 to 5 was prepared using the vinyl copolymers (P-2) to (P-5) shown in Table 1. All were carried out under temperature and humidity conditions of mixing temperature 20°C and RH 60%.
[0042] Examples 6 to 10 Using ordinary Portland cement under the mix conditions (mix number 2, no fluoride) shown in Table 2, concrete of Example 6 was prepared with a water-cement ratio of 50%, a target slump of 18±1 cm, and a target air content of 4±1%, in the same manner as in Example 1. Similarly, concretes of Examples 7 to 10 were prepared using the vinyl copolymers (P-2) to (P-5) shown in Table 1.
[0043] Examples 11 to 15 Concrete of Example 11 was prepared under the mix conditions (mix number 3, containing potassium fluoride) shown in Table 2, with a water-cement ratio of 35%, a target slump of 21±1 cm, and a target air content of 4±1%, in the same manner as in Example 1. Similarly, concretes of Examples 12 to 15 were prepared.
[0044] Examples 16 to 20 Using ordinary Portland cement having the mix conditions (mix number 4, containing no fluoride) shown in Table 2, concrete of Example 16 was prepared with a water-cement ratio of 35%, a target slump of 21±1 cm, and a target air content of 4±1%, in the same manner as in Example 11. Similarly, concretes of Examples 17 to 20 were prepared.
[0045] Examples 21 to 25 Using the mix conditions shown in Table 2 (mix number 5, containing potassium fluoride), blast-furnace cement type B (density = 3.03 g / cm3) was mixed in a 50-liter pan-type forced mixer. 3 0.5 parts of potassium fluoride was added to 100 parts of cement), fine aggregate (river sand, density = 2.58 g / cm 3 ), mixing water (tap water) and the necessary amount of antifoaming agent and air content regulator were added and mixed for 90 seconds until the slurry became uniform. Next, coarse aggregate (crushed stone, density = 2.68 g / cm 3 ) was added and mixed for 60 seconds. The same method as above was used to prepare concrete of Example 21 with a water-cement ratio of 45%, a target slump of 21±1 cm, and a target air content of 4±1%. Concretes of Examples 22 to 25 were also prepared in the same manner.
[0046] Examples 26 to 30 Using the mix conditions (mix number 6, no fluoride) shown in Table 2, concrete of Example 26 was prepared with a water-cement ratio of 45%, a target slump of 21±1 cm, and a target air content of 4±1%, in the same manner as in Example 21, using blast-furnace cement type B. Similarly, concretes of Examples 27 to 30 were prepared.
[0047] Comparative Examples 1 to 5: Concrete was prepared in the same manner as in Examples 1 to 5. Comparative Examples 6-10: Concrete was prepared in the same manner as in Examples 6-10. Comparative Examples 11-15: Concrete was prepared in the same manner as in Examples 11-15. Comparative Examples 16-20: Concrete was prepared in the same manner as in Examples 16-20. Comparative Examples 21-25: Concrete was prepared in the same manner as in Examples 21-25. Comparative Examples 26-30: Concrete was prepared in the same manner as in Examples 26-30.
[0048] [Table 2]
[0049] In Table 2, *1: Cement with 1 part calcium fluoride added to 100 parts of ordinary Portland cement *2: Ordinary Portland cement (density = 3.16 / cm 3 ) *3: Cement to which 1 part of potassium fluoride is added to 100 parts of blast furnace cement type B *4: Blast-furnace cement type B (density = 3.03 / cm 3 ) *5: Fine aggregate (river sand, density = 2.58g / cm 3 ) *6: Coarse aggregate (crushed stone, density = 2.68g / cm 3 )
[0050] -Evaluation of concrete properties The concrete prepared in each example was evaluated for slump, air content, and compressive strength immediately after mixing and after leaving for 90 minutes using the methods described below, and the physical property test results are summarized in the table. Slump (cm): Measured in accordance with JIS-A1101 for concrete immediately after mixing and after leaving to stand for 90 minutes. Slump remaining rate (%): Slump value after standing for 90 minutes / Slump value immediately after mixing) x 100. Air content (volume %): Measured in accordance with JIS-A1128 for concrete immediately after mixing and after leaving to stand for 90 minutes. Compressive strength (N / mm 2 ):Measurements were carried out in accordance with JIS-A1108 for hardened specimens aged 1 day, 3 days, and 28 days.
[0051] The test results of the fresh (before hardening) concrete of Examples 1 to 30 are summarized in Table 3, and the test results of the hardened concrete are summarized in Table 4. The test results of the fresh concrete of Comparative Examples 1 to 30 are summarized in Table 5, and the test results of the hardened concrete are summarized in Table 6.
[0052] [Table 3]
[0053] [Table 4]
[0054] In Tables 3 and 4, *1: Formulation number listed in Table 2 *2: Water-soluble vinyl copolymers listed in Table 1 *3: Parts of water-soluble vinyl copolymer (solid equivalent) added per 100 parts by mass of cement *4: - parts were not measured.
[0055] [Table 5]
[0056] [Table 6]
[0057] In Tables 5 and 6, *1: Formulation number listed in Table 2 *2: Water-soluble vinyl copolymers listed in Table 1 *3: Parts of water-soluble vinyl copolymer (solid equivalent) added per 100 parts by mass of cement *4: The parts marked with - had not hardened when the material was removed from the formwork and therefore could not be measured.
[0058] As is clear from the results of Tables 1 to 6, concrete prepared using the cement dispersant made of the water-soluble vinyl copolymer according to the present invention has the intended performance of imparting high fluidity to fresh concrete, reducing slump loss, and excellent early strength development of the hardened concrete, even when fluoride-containing ordinary Portland cement or fluoride-containing blast furnace slag cement is used. The present invention also has the characteristic of being able to prepare high-quality concrete even when fluoride-free cement is used.
Claims
1. A hydraulic cement composition comprising at least cement, aggregate, water and the following cement dispersant, characterized in that the content of the cement dispersant is 0.05 to 2.5 parts by mass per 100 parts by mass of cement. Cement Dispersant: A cement dispersant comprising a water-soluble vinyl copolymer obtained by copolymerizing in an aqueous solution a monomer A represented by the following chemical formula 1, a monomer B represented by the following chemical formula 2, a monomer C represented by the following chemical formula 3, and a monomer D represented by the following chemical formula 4, the copolymerization ratio calculated as monomers being represented by the following chemical formula 1 / monomer B represented by the following chemical formula 2 / monomer C represented by the following chemical formula 3 / monomer D represented by the following chemical formula 4=55-88 / 0.5-10 / 0.5-10 / 8-25 (mol %, total 100), and the mass average molecular weight being in the range of 3,000 to 100,000. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In Chemical Formula 1 to Chemical Formula 4, R 1 , R 2 , R 1 , R 3 , R 4 , : H or CH 3 . R 5 : an alkyl group having 1 to 3 carbon atoms. M 1 : Hydrogen or an alkali metal or an alkaline earth metal. n: an integer from 1 to 3. m: an integer from 4 to 95.
2. The cement dispersant according to claim 1, wherein the monomer D represented by Chemical formula 4 is a mixture containing two kinds of monomers, a monomer having an added mole number of ethylene oxide in the range of 5 to 30 and a monomer having an added mole number in the range of 31 to 80.
3. The hydraulic cement composition according to claims 1 and 2, wherein the cement dispersant is a water-soluble vinyl copolymer having a copolymerization ratio of monomer A represented by Chemical formula 1 / monomer B represented by Chemical formula 2 / monomer C represented by Chemical formula 3 / monomer D represented by Chemical formula 4 = 60-80 / 1-7 / 1-8 / 9-24 (mol%, total 100).
4. The hydraulic cement composition according to any one of claims 1 to 3, wherein the cement is Portland cement.
5. 5. The hydraulic cement composition according to claim 1, wherein the cement is a mixed cement comprising Portland cement and ground granulated blast furnace slag.
6. The hydraulic cement composition according to any one of claims 1 to 5, which is a cement containing an inorganic fluoride in the range of 0.05 to 10 mass %.
7. The hydraulic cement composition according to any one of claims 1 to 6, wherein the inorganic fluoride is at least one selected from the group consisting of KF, CaF2, NaF, BaF2, MgF2, Na2SiF2, and MgSiF2 fluorides.
8. The hydraulic cement composition according to any one of claims 1 to 7, wherein the hydraulic cement composition is concrete.
9. Unit water volume: 120-180 kg / m 3 The hydraulic cement composition according to claim 8, wherein the water-binder ratio of the concrete is 20 to 65%.
Citation Information
Patent Citations
Radiation-spectrum measuring apparatus
JP1993011057A
Dispersing agent for cement
JP1999171619A
Cement dispersing agent
JP2003002720A
Admixture for blast furnace slag concrete, and method for preparing blast furnace slag concrete
JP2013112565A
Additive for cement
JP2017178775A